Analisis Implementasi Perencanaan Audit Laporan Keuangan Berdasarkan Standar Profesional Akuntan Publik pada KAP FAR - Dimas Febri Ardiansah; Irawan Irawan; Nurmala Nurmala (Politeknik Negeri Lampung, 2021)
This writing aims to analyze the audit planning of KAP FAR's financial statements, whether it is in accordance with the Professional Standards of Public Accountants (SPAP). If it is appropriate to find out whether KAP FAR implements kap far financial statement audit planning. In the preparation of this final task the author uses qualitative methods and the type of data used is primary data. The results of the discussion of this final task show that KAP FAR makes audit planning papers in accordance with the Professional Standards of Public Accountants (SPAP). However, there are some that are not implemented by KAP FAR, namely analytical procedure working paper, audit team personnel, and audit risk setting.